An Overview of Outpatient Hysteroscopy - Natalia Ignaszak-Kaus; Karolina Chmaj-Wierzchowska; Adrian Nowak; Katarzyna Wszołek; Maciej Wilczak (IMR Press, 2022)
Objective: Hysteroscopic procedures are minimally invasive procedures that enable to assess the uterine cavity (diagnostic hysteroscopy) and to treat intrauterine lesions (operative hysteroscopy). In recent years have witnessed a steady increase in the number of procedures performed via minimally invasive surgery (MIS) including hysteroscopies. Most outpatient hysteroscopies are painless, without complications, and not only allow to diagnose but also treat several intrauterine pathologies. Vaginoscopy hysteroscopy without using speculum, tenaculum and other potentially painful instrumentation should become the default method for outpatient hysteroscopy. This 'no-touch' technique is faster in contrary to standard hysteroscopy and is associated with less pain. Mechanism: A wide range of feasible procedures, constantly improved endoscopic equipment and tools, improving the technical conditions of the procedure, as well as short hospitalization time and a quick recovery period, are just some of the benefits of hysteroscopic surgeries. Findings in Brief: Performing hysteroscopy in an outpatient setting without general anesthesia addictionally reduces treatment cost and avoid of possible complications of general anesthesia. Conclusions: Performing hysteroscopy in an outpatient setting without general anesthesia (with the patient's consciousness preserved during the surgery) reduces treatment cost and shortens the duration of hospitalization and convalescence, thus increasing patient satisfaction with care.